Nomenclatural notes on marantaceae described by Édouard Morren - Saka, Mariana Naomi [UNESP]; de Moraes, Pedro Luís Rodrigues [UNESP]; Lombardi, Julio Antonio [UNESP]; Diagre-Vanderpelen, Denis (Magnolia Press, 2017)
The species of Marantaceae described by Édouard Morren are cultivated due to the ornamental value of their leaves. On account of the widely use of these names for horticultural purposes, the taxa proposed by Morren were reviewed. A total of ten lectotypes, seven epitypes and six neotypes are designated, as well as three lectotypes and two neotypes for species indicated as synonyms of Morren names. We also propose the combination of Calathea lietzei, C. kegljani and C. wiotiana in Goeppertia, the latter due to a previous invalid combination. A new name for the illegitimate C. pulchella is also indicated. Calathea mirabilis was described without an illustration or known material and therefore the application of this name is considered uncertain.
Keywords: Calathea; Ctenanthe; Goeppertia; Horticulture; Maranta; Typification